OPTIMASI PENGALOKASIAN AIR BENDUNG PANDANDURI DALAM PENINGKATAN PENDAPATAN PETANI DI DAERAH IRIGASI PANDANDURI KABUPATEN LOMBOK TIMUR - , Ikroman Alhamzani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Irrigation area of Pandanduri is part of the irrigation system of Pandanduri Suangi, which the main water resource is River of Palung, through the main intake of Pandanduri Dam. Lack of water resources availability on River of Palung, especially in dry season, cannot fulfill the water demand of several paddy fields. To solve this problem, some ponds were constructed in the downstream of the Pandanduri Reservoir, combined with the main channel system of Pandanduri. These ponds are called Pond of Ujung and Pond of Lingkoq Lamun. In this research, study of water allocation optimization to increase the farmer income was conducted to obtain the optimal capability and reliability of the water allocation, and then would income based on water balance in channel system of Pandanduri. Analysis of water use optimization of Pandanduri Dam, Ujung Pond and Lingkoq Lamun Pond was conducted using Liniear Programing Method and combined with simulation technique of water release operation from the pond. Simulation of Pandanduri Dam, Ujung Pond, and Lingkoq Lamun Pond operation were conducted in 3 scenarios of discharge, first scenario using existing discharge of 2011, second scenario using reliable intake discharge of Pandanduri Dam (1992- 2010), and third scenario using water release discharge of Pandanduri Reservoir (Abdul Azis, 2012). In each scenario these several condition were applied, first condition is simulation without considering the return flow, second condition is simulation by considering the return flow, and third condition is simulation by considering the return flow and supply for Irrigation Area of Gambir (Pond of Inen Ratu). In the calculation process, inflow that enters the pond is water excess after fulfilling irrigation demand from the upstream area of Pandanduri. Research result shows that the return flow value can increase the water utilization of Pandanduri Dam. Using the planting system of paddy-paddy/cropscrops, planting intensity in 200% (existing condition), and discharge value of 2011, the reliability of Ujung Pond and Lingkoq Lamun Pond with initial planting on January are 100%, and the value of k factor for each pond are 1,00. While for the designed condition using planting system of paddy-paddy/crops-crops and planting intensity in 300%, simulation was conducted using water release data of Pandanduri Reservoir and initial planting on October, the reliability of Ujung Pond and Lingkoq Lamun Pond are 100% and 87.50%, and the k factor of each pond are 1,00 and 0,91. The profit from the optimization are increasing of farmer net income in amount of 23.14% compare to the existing income.